2014
DOI: 10.1021/jp504139j
|View full text |Cite
|
Sign up to set email alerts
|

Microhydration of Contact Ion Pairs in M2+OH(H2O)n=1–5 (M = Mg, Ca) Clusters: Spectral Manifestations of a Mobile Proton Defect in the First Hydration Shell

Abstract: Vibrational predissociation spectra of D2-"tagged" Mg(2+)OH(-)(H2O)n=1-6 and Ca(2+)OH(-)(H2O)n=1-5 clusters are reported to explore how the M(2+)OH(-) contact ion pairs respond to stepwise formation of the first hydration shell. In both cases, the hydroxide stretching frequency is found to red-shift strongly starting with addition of the third water molecule, quickly becoming indistinguishable from nonbonded OH groups associated with solvent water molecules by n = 5. A remarkably broad feature centered around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 39 publications
6
57
0
Order By: Relevance
“…This series of transition metals bridge the gap between the Mg and Ca complexes studied by Johnson et al 17 and the Cu complex studied previously in our group. 11 The evolution of the vibrational frequencies of the hydroxide and water ligands as a function of the metal center sheds light on the gradual charge transfer behavior of this series of metals.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This series of transition metals bridge the gap between the Mg and Ca complexes studied by Johnson et al 17 and the Cu complex studied previously in our group. 11 The evolution of the vibrational frequencies of the hydroxide and water ligands as a function of the metal center sheds light on the gradual charge transfer behavior of this series of metals.…”
Section: Discussionsupporting
confidence: 53%
“…The experimental values for the hydroxide frequency of the Mg and Ca complexes are obtained from ref. 17. The red line is a linear fit of the data points excluding the Zn complex.…”
Section: Discussionmentioning
confidence: 99%
“…At the low temperatures relevant for the present experiments, the dominant quantum effect is zero-point motion, which is known to couple soft modes to strongly H-bonded stretches. 99,100 We believe that this is a major factor responsible for the large widths of the features associated with the hydronium OH stretch vibrations in the cold clusters. Important future directions will involve a more quantitative explanation for the spectral breadth as well as determination of the temperature dependence of the spectral patterns.…”
Section: Feature Articlementioning
confidence: 94%
“…99,100 A more detailed analysis on the origins of the spectral breadth is clearly warranted but is beyond the scope of this article. VI.…”
Section: Feature Articlementioning
confidence: 99%
“…[46][47][48] Stace and co-workers showed that many complexes of Pb(II) with organic ligands are stable in the gas phase, 49,50 but that gaseous clusters of Pb 2+ (H 2 O) n are unstable to hydrolysis for n o 11 and consequently are not present in electrospray ionization (ESI) mass spectra. 52 IRPD studies of ion pair hydrates have so far been limited to two reports on the first hydration shell of metal hydroxides, 53,54 and a report on [MgNO 3 ] + (H 2 O) [1][2][3][4] . 52 IRPD studies of ion pair hydrates have so far been limited to two reports on the first hydration shell of metal hydroxides, 53,54 and a report on [MgNO 3 ] + (H 2 O) [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%